Bilateral compartment of the hands in prolidase deficiency syndrome - Raphael Tasar; Philipp Alexander Bergmann; Waltraud Anemüller; Alexander Herz; Philipp Neis; Peter Mailänder (Elsevier, 2021)
Background: We report the Case of Prolidase - deficiency syndrome in a 3-year-old boy suffering from atraumatic compartment syndrome in both hands. Case description: We discuss four areas of controversy. First, what could be the reason for an atraumatic compartment syndrome in both hands?Second, should we operate on a 3-year-old boy or use a conservative approach? Third, would we have chosen an operative approach knowing the underlying condition? Fourth, how should we proceed postoperatively? Conclusion: We chose to operate him and performed a compartment release operation. He was treated interdisciplinary and discharged after fifteen days.